2022
DOI: 10.3390/cancers14174241
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Disease and Survival in Oral Cancer: Is Occult Metastasis a Burden Factor Compared to Preoperatively Nodal Positive Neck?

Abstract: The impact of neck involvement and occult metastasis (OM) in patients with oral squamous cell carcinoma (OSCC) favors an elective neck dissection. However, there are barely any existing data on survival for patients with OM compared with patients with positive lymph nodes detected preoperatively. This study aims to compare survival curves of patients suffering from lymph nodal metastases in a preoperatively N+ neck with those suffering from OM. In addition, clinical characteristics of the primary tumor were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…SUVmax of the primary tumor was found to be the most powerful parameter according to its diagnostic performance. These findings are consistent with those of previous studies reporting that the biologic and radiographic characteristics of the primary tumor are factors related to lymph node metastasis [2,[24][25][26][27]. A recent study revealed that a higher tumor grading increased the chance of metastasis by 2.7 times [2].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…SUVmax of the primary tumor was found to be the most powerful parameter according to its diagnostic performance. These findings are consistent with those of previous studies reporting that the biologic and radiographic characteristics of the primary tumor are factors related to lymph node metastasis [2,[24][25][26][27]. A recent study revealed that a higher tumor grading increased the chance of metastasis by 2.7 times [2].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with those of previous studies reporting that the biologic and radiographic characteristics of the primary tumor are factors related to lymph node metastasis [2,[24][25][26][27]. A recent study revealed that a higher tumor grading increased the chance of metastasis by 2.7 times [2]. Tumor grading is based on histopathological characteristics, including the degree of resemblance to normal tissues.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…OSCC is a malignant tumor with high morbidity and mortality and is a threat to human health (16). OSCC often involves the tongue and lips, and can easily spread to other organs, including the lungs and lymph nodes (17)(18)(19). The lack of specific detection of OSCC tumor boundaries makes it difficult to determine the extent of disease at the time of treatment and often adversely affects a patient's appearance and quality of life after surgery (20).…”
Section: Discussionmentioning
confidence: 99%